Assessment of Pollution Linked to Surface-Active Materials and Nutrients in Lotic Ecosystem - Rana R. Al-Ani; Zahraa Z. Al-Janabi; Fikrat M. Hassan; Abdul-Hameed M. Jawad Al-Obaidy; Ali N. Al-Aamel; Ahmed Al-Taie (Salehan Institute of Higher Education, 2026)
The Tigris River is one of the main rivers and an important resource for the population of Iraq. The present study aimed to quantify the concentration of surface-active substances in the Tigris River and to investigate the dynamics of this ecosystem. Five sampling sites were selected along the river within Baghdad city (Al-Muthanna Bridge, Al-Greaat Bridge, Al-Sarrafia Bridge, Al-Jadriyah Bridge, and Al-Za'franiya Area) for the period from July 2020 to April 2021. The study examined the relationship between the concentrations of surface-active materials (surfactants, including anionic and nonionic types) and their potential interaction with nutrients—nitrate (NO₃⁻), phosphate (PO₄), and sulfate (SO₄²⁻)—as well as the influence of various physicochemical water parameters on surfactant concentrations. The results of the descriptive analysis of water parameters during the dry and wet seasons showed variations and elevated concentrations of some parameters beyond permissible limits, such as TDS, NO₃⁻, PO₄, SO₄²⁻, and DO. According to the OIP analysis, only Site 2 (Al-Greaat Bridge) was classified as polluted (Class-C4) during the wet season (6.58), while the other sites were categorized as slightly polluted (Class-C3) in both dry and wet seasons. Principal component analysis (PCA) indicated that PO₄, TDS, and NO₃⁻ were the most influential parameters and had a strong positive relationship with anionic surfactants. Regarding temporal variation, higher values of TDS, NO₃⁻, PO₄, SO₄²⁻, and DO were observed during the dry season. This reflects the impact of human activities (agriculture, industrial discharge, and sewage effluents) and natural processes (rainfall, evaporation, and biological activity) on the water quality of the Tigris River. Therefore, the Tigris River faces significant water quality challenges due to both anthropogenic and natural factors. Effective management strategies are essential to mitigate these impacts and protect the health of the river ecosystem and the communities that depend on it. The findings of this study align with Sustainable Development Goal (SDG) 6, which focuses on clean water and sanitation.